Stosunek administracyjnoprawny w niemieckiej doktrynie prawa publicznego - Sancewicz, Paweł (Uniwersytet im. Adama Mickiewicza w Poznaniu, 2020)
The notion of the administrative-legal relationship is the basis of the dogmatics of Polish administrative law. Over the years, the doctrinal framework of this concept has been established by the doctrine of public law. At the same time, an extremely fruitful dogmatics discussion about this concept both in German law and practice has taken place. Therefore, the article attempts to present discoveries of the German doctrine of public law in this area. The review of the German literature conducted in the article shows that, despite some disputes, the German authors currently believe that the administrative-legal relationship is a useful tool for the analysis of rights and obligations in comprehensive legal relations, as well as cooperative frameworks. Contemporary German scholars, who do not distinguish the concept of a legal situation, unlike in Poland, believe that as part of the modernization processes in administration, the concept of the administrative-legal relationship can be used to solve complex legal issues.The above-mentioned discoveries made by German scholars could act as significant inspiration for the Polish doctrine of public law, especially in the context of the draft to introduce an administrative agreement into Polish law. Of particular importance here is the fact that in Germany there is a different system of the legal forms of administration activity, of which an administrative agreement is a vital component. It is indicated in the paper that Polish scholars see the possibility of describing complex legal constructions by the notion of the administrative-legal relationship in the simultaneous or complementary use of the concept of the administrative-legal situation. One should consider whether the same or better effects cannot be achieved much more easily, namely by modifying the understanding in the doctrine of the notion of administrative-legal relationship, more appropriate to the analysis of cooperative frameworks in administration.
Keywords: administrative; legal relationship; legal forms of administrative activity; administrative procedure; public subjective rights; administrative contract